Kepemimpinan Adaptif Dalam Dunia Digital: Mengatasi Tantangan Dan Peluang Di Era 4.0 - Cahyati Wulandari , Desy; Sri Pudjiarti, Emiliana (Universitas 17 Agustus 1945 Semarang, 2024)
The digital era has created new challenges for leaders in terms of complexity and caused very rapid changes. Adaptive leadership is crucial so that organizations can adapt to digital transformation. This article aims to understand the effective implementation of digital adaptive leadership, specific challenges and opportunities, its contribution to business desires, core competencies, as well as achieving strategic alignment. Digital leaders must be agile and continuously learn to overcome challenges such as the complexity of the business environment and the speed of technology and innovation adoption. They also need to encourage a culture of agility and risk-taking. Core competencies include the ability to build multicultural teams, ethical leadership in data use, and maintaining digital alignment strategies. Continuous training is needed so that leaders have the skills to meet the demands of the digital era.